Interactive effects of dietary fishmeal level and plant essential oils supplementation on European sea bass, Dicentrarchus labrax: Growth performance, nutrient utilization, and immunological response. Issue 6 (7th May 2019) - Gonçalves, Rui A.; Serradeiro, Renata; Machado, Marina; Costas, Benjamin; Hunger, Christine; Dias, Jorge
Abstract: The inclusion of phytogenics in fish feed is a promising strategy to compensate for the negative performance effects of replacing fishmeal (FM) with vegetable sources. The present work assessed the interactive effects of different dietary FM levels (22.5 and 10% of formulation) and the supplementation of a commercial blend of anise, citrus, and oregano essential oils (Digestarom PEP M.G.E 150) on European sea bass, Dicentrarchus labrax growth performance, nutrient utilization, gut morphology, antioxidant status, and immunological response over a 60‐day growth trial. Results showed decreased growth and protein efficiency ratio and increased feed conversion ratio with a low dietary FM level. In contrast, supplementation of the phytogenic product demonstrated improved performance and nutrient utilization together with increased protein and energy retention. Supplementation with the plant essential oils fully compensated for the negative intestinal changes observed in sea bass fed a low‐FM diet but showed little improvement in fish immunological response, except for the 30% increase in lysozyme activity observed in fish fed the low FM‐supplemented diet compared to those fed the standard high‐FM diet. Overall, this study supports the use of this phytogenic product in low‐FM diets as a possible tool to decrease feed costs associated with FM without compromising fish performance, nutrient utilization, and health.